'The Good, the Bad and the Ugly': A Model for Reflective Teaching Practices in Coaching Pedagogy. (2nd January 2017) - Gordon, Evelyn J.
Abstract : Coaching should go beyond drills and preparing for the big game. One question many coaches have asked themselves is, "How do I get better?" One way to ensure that future coaches (current students) in sport coaching education are thinking of ways to improve for the future is to teach them to think about the past. This is where reflection comes into play. "The Good, the Bad and the Ugly" is a presentation of reflective practices used during a sport pedagogy course to evaluate coaching demonstration.